Comment on: "A structured pathway for accelerated postoperative recovery reduces hospital stay and cost of care following microvascular breast reconstruction without increased complications". Issue 2 (February 2021) - Chin, Ye Ru; Waters, Ruth; Srinivasan, Karthikeyan; Warner, Robert
Summary: We read with great interest a recent article by O'Neill et al. on the implementation of an accelerated postoperative recovery protocol following DIEP flap breast reconstruction. Our department has formally introduced a DIEP Enhanced Recovery After Surgery (ERAS) Pathway in May 2019. Although in a much smaller sample size, our results were similar to this article and we would agree with the authors' conclusion that implementation of such protocol could effectively reduce the length of inpatient stay (LoS) and cost of care, without compromising patient care nor increasing complication rates. Prior to the introduction of ERAS Pathway, 28 of our patients who had DIEP between November 2018 and May 2019 had an mean LoS of 7.1 days (median 6 days, range 5–21 days); whereas 27 patients who experienced the ERAS Pathway between May and December 2019 had an mean LoS of 4.8 days (median 5 days, range 3–7 days). The cost of inpatient stay in a normal ward at our hospital is approximately £232 per patient per day. By reducing an extra 2.3 days of inpatient stay, our Trust could save at least an average of £32, 016 per annum with the estimated 60 DIEP performed annually at our department. We would like to emphasise the benefits and effectiveness of this multimodal, patient-centre and evidence-based ERAS. This, perhaps, should be the standard of care for all patients who undergo microvascular breast reconstruction in the future.